Discussion on the future of Irish external trade - Kennedy, Henry; Johnston, Joseph; O'Hegarty, P. S.; Edgeworth, K. E.; O Coineain, A.; Mortished, R. J. P.; Meenan, James; Geary, R. C.; Beddy, J. P. (Statistical and Social Inquiry Society of Ireland, 1944)
Dr. Henry Kennedy said that his contribution to the Discussion would take the form of a detailed estimate of the productive potential of our land. He would leave to other speakers consideration of the economic and perhaps political pre-requisites for the attainment, in whole or in part, of the estimates which he put forward. An estimate is made of what production might be obtained from the land of the country, assuming that it is farmed with adequate knowledge, skill and adequate capital resources for equipment and essential raw materials. In order to simplify the problem, it is assumed that the foods for man and beast are home produced; and that no feed for animals is imported. The object is to give a picture of what might be achieved on the assumption of various crop yields.
Held on Thursday, 21th April, 1944
Keywords: Agricultural exports; International trade; 314.15